Incidence of Severe Infections and Infection‐Related Mortality During the Course of Giant Cell Arteritis: A Multicenter, Prospective, Double‐Cohort Study. Issue 6 (26th May 2016) - Schmidt, J.; Smail, A.; Roche, B.; Gay, P.; Salle, V.; Pellet, H.; Duhaut, P.
Abstract : Objective: To assess the incidence of infections leading to hospitalization, the mortality rate related to infections, and the determinants of these factors in patients with giant cell arteritis (GCA). Methods: In total, 486 patients with GCA (75% women) were enrolled at the time of diagnosis. All patients fulfilled the American College of Rheumatology criteria for GCA. As controls, age‐ and sex‐matched subjects were randomly selected from the general population and matched to patients at the time of diagnosis of GCA. Both groups were prospectively followed up over a 5‐year period. Results: Severe infections were more frequent among patients with GCA during the first year after diagnosis, compared to general population controls (incidence rate ratio 2.1, 95% confidence interval [95% CI] 1.2–3.4; incidence rate 11.1/100 patient‐years [95% CI 8.3–14.6] in patients with GCA versus 5.9/100 patient‐years [95% CI 4–8.4] in controls). Specifically, septic shock and infectious colitis were more frequent among the patients with GCA. Mortality caused by infections was higher in patients with GCA compared to controls ( P < 0.0001 by log rank test). In analyses adjusted for age, among patients with GCA, a diagnosis of diabetes (hazard ratio [HR] 3.3, 95% CI 1.4–7.7) and a corticosteroid dosage that was >10 mg/day after 12 months of treatment (HR 4.61, 95% CI 1.38–15.36) were associated with death attributed to severe infection. The observed overall incidence of mortality was increased in patients with GCA during the early period of enrollment in the study (before 1997) ( P = 0.0001 by log rank test), but thereafter was the same as that in the general population controls. Conclusion: Frequencies of severe infections and rates of infection‐related mortality are increased during the first year after the diagnosis of GCA. The risk of infection increases in GCA patients with older age or in the presence of diabetes, or is greater when the dosage of corticosteroids has been increased to >10 mg/day after 12 months of treatment.